Integrated Marketing Communication Evaluation Based on CIPP Model of Webinars At PT. XYZ - Jasinda, Jasinda; Dewanti, Retno; Bogonikolos, Nikos (SEEIJ (Social Economics and Ecology International Journal), 2023)
This research is based on the application of an integrated marketing communication through one of the alternative media as a form of marketing, namely webinars. In this pandemic era, where it is required to maintain a distance, and at the same time the marketing process must continue, the use of technology must be maximized. The purpose of this research is to help PT. XYZ in solving problems at hand and assisting in the application of marketing communications through alternative media, namely webinars through analysis of the CIPP model and applying a priority scale in a webinar. The evaluation method used in this final project is conjoint analysis. From the results obtained, it was found that the most important factors in holding a webinar were social factors and emotional satisfaction in the evaluation of the ongoing process. From the results of the analysis obtained, further evaluation is carried out based on company data. After that, a performance improvement design is carried out which is stated in a performance indicator to improve other factors. So that these indicators can be used to increase brand awareness and lead generation for company.